(untitled) (Romanian Journal of Analytic Philosophy, 2024)
In this paper I sketch two solutions to Pinocchio’s Paradox, mainly by resorting to the concept of lying, as it is conceived by Augustine in his “De mendacio”. I will argue that the paradox is based on a slightly narrow conception of what it means to lie, as it confuses the meaning of lying with the meaning of falsity from the correspondence theory of truth. Furthermore, I will claim that the problems that I have highlighted are sufficient conditions to block the entire paradox and, therefore, to show that the argument that supposedly leads to a contradiction is actually fallacious.